1997
DOI: 10.1002/(sici)1098-2744(199710)20:2<204::aid-mc7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes associated with chemically induced rat mammary carcinogenesis

Abstract: Experimentally induced models of breast carcinogenesis in the rat are widely used for studying the biology of breast cancer and for developing and evaluating cancer prevention and control strategies. However, very little is known about gene expression changes that are associated with experimentally induced mammary carcinogenesis. This paper reports the identification, by differential display of mRNA and molecular cloning, of seven cDNA fragments of gene transcripts overexpressed in mammary carcinomas induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 45 publications
1
50
1
Order By: Relevance
“…However, PPARγ overexpression in mouse liver enhances SCD1 expression (10), while PPARγ deficiency reduces it (36). Several treatments or conditions that are associated with hepatocarcinogenesis (57, 59) also increase SCD1 expression, and SCD1 levels are higher in rat mammary carcinomas (60) and in mice that are genetically susceptible to hepatocarcinogenesis (61). Sterculic acid, an inhibitor of SCD1 activity, blocks rat mammary carcinogenesis (62).…”
Section: Discussionmentioning
confidence: 99%
“…However, PPARγ overexpression in mouse liver enhances SCD1 expression (10), while PPARγ deficiency reduces it (36). Several treatments or conditions that are associated with hepatocarcinogenesis (57, 59) also increase SCD1 expression, and SCD1 levels are higher in rat mammary carcinomas (60) and in mice that are genetically susceptible to hepatocarcinogenesis (61). Sterculic acid, an inhibitor of SCD1 activity, blocks rat mammary carcinogenesis (62).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of this enzyme and consequently high levels of oleic acid has been shown to be required for tumor development in experimental animal studies. [41][42][43] ⌬9-d activity is modulated by several dietary factors: saturated fatty acids, cholesterol and carbohydrates stimulate this enzyme, whereas dietary polyunsaturated fatty acids and fasting are depressors. 37 Individual animal 3 and epidemiological studies 44 -45 have generally shown that olive oil has either no effect or a protective effect on breast cancer risk, which were initially attributed to its high content of the monounsaturated fatty acid, oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 The role of galectin-7 in cancer has previously been implied in a rat model of chemically induced mammary carcinoma. 22 Galectin-7 was originally identified in the human epidermis and later found to be expressed in all types of stratified epithelial cells in the skin, tongue, esophagus, and Hassal's corpuscles in the thymus. 20,21,25 In skin keratinocytes, its expression is rapidly induced following exposure to UV irradiation in association with p53 stabilization, and an increased level of the protein was mainly found in sunburned apoptotic keratinocytes.…”
Section: Figurementioning
confidence: 99%
“…Among those genes whose expression were significantly altered, we further investigated the unexpected and strongly upregulated galectin-7. This gene, originally identified as a keratinocyte marker, 20,21 has previously been associated with the development of chemically induced mammary carcinoma 22 and is one of the 14 genes previously shown to be under the control of p53. 23 …”
Section: Introductionmentioning
confidence: 99%